Bridging Methods for Atomistic-to-Continuum Coupling and Their Implementation (Communications in Computational Physics, 2010)
Several issues connected with bridging methods for atomistic-to-continuum(AtC) coupling are examined. Different coupling approaches using various energyblending models are studied as well as the influence that model parameters, blendingfunctions, and grids have on simulation results. We use the Lagrange multipliermethod for enforcing constraints on the atomistic and continuum displacements inthe bridge region. We also show that continuum models are not appropriate for dealingwith problems with singular loads, whereas AtC bridging methods yield correctresults, thus justifying the need for a multiscale method. We investigate models thatinvolve multiple-neighbor interactions in the atomistic region, particularly focusing ona comparison of several approaches for dealing with Dirichlet boundary conditions.